1990
DOI: 10.1038/347491a0
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase II C-terminal repeat influences response to transcriptional enhancer signals

Abstract: The large subunit of RNA polymerase II contains a highly conserved and essential heptapeptide repeat (Pro-Thr-Ser-Pro-Ser-Tyr-Ser) at its carboxy terminus. Saccharomyces cerevisiae cells are inviable if their RNA polymerase II large subunit genes encode fewer than 10 complete heptapeptide repeats; if they encode 10 to 12 complete repeats cells are temperature-sensitive and cold-sensitive, but 13 or more complete repeats will allow wild-type growth at all temperatures. Cells containing C-terminal domains (CTDs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
145
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(148 citation statements)
references
References 30 publications
2
145
0
Order By: Relevance
“…Pol II at the stage of transcription initiation is associated with a large holoenzyme complex, which is recruited to promoters by sequence-specific transcriptional activators (6 -10). In some cases, stimulation of transcription by activators requires the CTD (11)(12)(13). Recent work has demonstrated that the CTD is also important for pre-mRNA processing.…”
mentioning
confidence: 99%
“…Pol II at the stage of transcription initiation is associated with a large holoenzyme complex, which is recruited to promoters by sequence-specific transcriptional activators (6 -10). In some cases, stimulation of transcription by activators requires the CTD (11)(12)(13). Recent work has demonstrated that the CTD is also important for pre-mRNA processing.…”
mentioning
confidence: 99%
“…For example, Pol II carrying altered CTDs responds differently to certain wildtype and mutant transcriptional regulators in vivo (Allison et al 1988;Scafe et al 1990;Peterson et al 1991), suggesting that the CTD may be involved in receiving regulatory signals at certain promoters. In vivo and in vitro experiments suggest that these responses might be mediated through the TATA-binding protein (TBP) component of TFIID (Koleske et al 1992;Usheva et al 1992; Thompson et al 1993).…”
mentioning
confidence: 99%
“…The CTD has been shown to carry out essential in vivo roles in yeast (Nonet et al 1987), Drosophila (Zehring et al 1988), and mammalian cells (Bartolomei et al 1988), but precisely what those roles are is not well understood. Suggested roles for the CTD include interacting with transcription initiation factors, serving as a molecular "cowcatcher" to facilitate movement of polymerase on chromatin templates, providing a link between transcription and RNA processing, and localizing polymerase to specific nuclear compartments (Corden 1990 (Allison et al 1988;Scafe et al 1990;Peterson et al 1991), suggesting that the CTD may be involved in receiving regulatory signals at certain promoters. In vivo and in vitro experiments suggest that these responses might be mediated through the TATA-binding protein (TBP) component of TFIID (Koleske et al 1992;Usheva et al 1992;Thompson et al 1993).…”
mentioning
confidence: 99%
“…The viral transactivating protein HBx interacts with RPB5 (46,47). Successive truncation of the C-terminal domain of RPB1 in yeast results in the decreased transcriptional induction from multiple genes and decreased response to specific activators (26,27), probably because of effects on the Pol II holoenzyme. An RPB5 point mutant similarly has decreased transcriptional induction of multiple genes, and RPB5 and C-terminal domain truncation double mutants are synthetically lethal, suggesting an overlap in function for the two subunits (28).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of individual Pol II subunits in yeast has revealed a role for a number of Pol II subunits in polymerase assembly (16)(17)(18)(19)(20), elongation (21,22), and accurate initiation of transcription (23)(24)(25). However, only the C-terminal domain of RPB1 and the full-length polypeptides of RPB5 and RPB7 have been shown to function in the stimulation of transcription from specific promoters (26)(27)(28)(29)). …”
Section: R Egulation Of Class II Gene Expression In Eukaryotes Involvesmentioning
confidence: 99%